Strategic integration of enriched metadata for the improvement of information systems management in a scientific journal - Michelle, Rojas Laguna Kelly; Torres, Arturo González; Romero, Vianey Ríos; Echeagaray, Melissa Edith Salazar (Edelweiss Applied Science and Technology, 2025)
This research is based on the inclusion of enriched metadata in an academic publication belonging to a public university that trains university students specialising in engineering. This institution is located in Mexico City. The objective was to positively impact its publishing activities. To this end, a qualitative paradigm was used, with a descriptive and exploratory level. The review focused on manuscripts published between 2019 and 2021. The investigation was carried out in three phases: preliminary evaluation, metadata homogenisation, and final assessment. The results showed an increase in compliance with metadata standards, which started at 57% and reached 100% at the end. Some of the most relevant conclusions were: the correct use of titles, abstracts, ORCID and DOI identifiers allowed academic publications to be integrated with search engines and academic platforms. The inclusion of rich metadata structures is an effective strategy for strengthening editorial quality and the international reach of publications.